2022
DOI: 10.1021/acsami.2c10348
|View full text |Cite
|
Sign up to set email alerts
|

Magnéli-Phase Ti4O7-Doped Laser-Induced Graphene Surfaces and Filters for Pollutant Degradation and Microorganism Removal

Abstract: Laser-induced graphene (LIG) has recently become a point of attraction globally as an environmentally friendly method to fabricate graphene foam in a single step using a CO 2 laser. The electrical properties of LIG are studied in different environmental applications, such as bacterial inactivation, antibiofouling, and pollutant sensing. Furthermore, metal or nonmetal doping of graphene enhances its catalytical performance in pollutant degradation and decontamination. Magneĺi phase (Ti n O 2n−1 ) is a substoich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 69 publications
5
38
0
Order By: Relevance
“…This can be attributed to the doped electrode's enhanced electrocatalytic and electrochemical activity on the application of voltage, which coincides with previous reports. 37,54 For T4 phage, increasing the doping concentration had no significant effect on the inactivation, as presented in Fig. 2e.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This can be attributed to the doped electrode's enhanced electrocatalytic and electrochemical activity on the application of voltage, which coincides with previous reports. 37,54 For T4 phage, increasing the doping concentration had no significant effect on the inactivation, as presented in Fig. 2e.…”
Section: Resultsmentioning
confidence: 84%
“…[32][33][34][35][36] In light of this, doping of titanium dioxide (TiO 2 ) in polyether sulfone (PES) polymers can generate sub-stoichiometric titanium dioxide (TiO x )-doped LIG on laser irradiation, which consists of unique electrical and optical properties. 37,38 However, studies on titanium suboxides such as Magnéli phase-based LIG composites are limited, necessitating their utilization for electrochemical inactivation of viruses.…”
Section: Introductionmentioning
confidence: 99%
“…17 The LIG method is a simple, reagent-free, solventfree, and single-step process of graphene formation on any carbonaceous substrate via laser scribing. [18][19][20] Due to graphene and its electroconductive nature, LIG filters and composite ECMs have shown good contaminant rejection and antibacterial, antiviral, and antibiofilm properties. [21][22][23][24][25] Detailed literature reviews on ECMs, LIG and their environmental application can be found elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Tour’s prepared a three-dimensional porous graphene (LIG) with excellent conductivity using polyimide (PI) as a carbon source through CO 2 laser direct writing . Subsequently, LIG was widely used as a 3D conductive graphene framework and combined with metals and their oxides via in-suit or post-modification methods, demonstrating immense potential in applications such as strain sensors, , electrodes, , supercapacitors, , etc. Chen et al obtained the synthesis of an in situ Cu nanoparticle-modified LIG-Cu composite material by incorporating copper salts into the PI precursor solution, resulting in a significantly enhanced conductivity of 0.37 × 10 7 S m –1 at low Cu loadings which is approximately 3000 times that of pure LIG.…”
Section: Introductionmentioning
confidence: 99%